Fiscal Concept for Handling Inflation according to Taqiyuddin An-Nabhani - Muhammad Sulthan Abimanyu Prakoso Putra (Penerbit Hellow Pustaka, 2026)
Inflation is a significant economic challenge in many countries, including Indonesia. In 2023, inflation in Indonesia reached 5.5%, far exceeding the 3±1% target. Conventional economic systems often struggle to manage inflation, whereas the Islamic economy offers alternative solutions. This study employs a literature review approach, analyzing the works of Taqiyuddin An-Nabhani—specifically An-Nizham Al-Iqtishadi fi Al-Islam (The Economic System in Islam) and *Al-Amwal fi Dawlat al-Khilafah* (Wealth in the Caliphate State). Data were gathered from books, journals, and relevant literature discussing An-Nabhani's Islamic economic thought. The findings indicate that the fiscal approach proposed by An-Nabhani emphasizes equitable wealth distribution through instruments such as zakat and price regulation. This system can help curb inflation by ensuring that wealth does not circulate solely among a select few, while also protecting the public's purchasing power. An-Nabhani highlights the state's crucial role in managing inflation through fiscal policies focused on economic balance and wealth distribution. These fiscal policies must be combined with monetary policies that regulate the money supply to achieve economic stability. A primary challenge lies in ensuring the effective implementation of wealth distribution policies within a modern economic context. Implementing An-Nabhani's theory requires structural reforms in the fiscal system, such as the management of zakat and tax reform. Furthermore, shifts in economic behavior and global market dynamics pose challenges to the application of this theory. Nevertheless, this approach offers the potential to mitigate economic instability and foster inclusive growth.